Negative extrathoracic pressure ventilation in central hypoventilation syndrome. Issue 5 (May 1994) - Hartmann, H; Jawad, M H; Noyes, J; Samuels, M P; Southall, D P
Abstract : Nine patients with central hypoventilation syndrome (CHS) were treated with negative extrathoracic pressure ventilation (VNEP). Treatment with VNEP was started between 20 days and 57 months of age, which was two days to 47 months after diagnosis. The equipment to provide VNEP utilised a new system with a latex neck seal and Perspex chamber allowing easy access to the child. Seven patients are managed with VNEP at home by their parents. They did not have a tracheostomy when VNEP was started at ages of 22, 24, 31, 38, and 75 days, 5 and 57 months. They have continued to be successfully managed with VNEP and without tracheostomy. Short periods of intubation and positive pressure ventilation were required on 10 occasions (median duration 7 days, range 4 to 21 days) in four subjects during respiratory tract infections. Three patients required periods of continuous positive airway pressure (CPAP) via a nasal mask or a nasopharyngeal airway during sleep to overcome upper airway obstruction. In three patients the hypoventilation improved and two of these do not require regular ventilatory support at 1.3 and 3.4 years of age. Six of these seven patients are developing normally. In two patients with long term tracheostomies, VNEP could not be established at an age of 29 and 52 months because of tracheal obstruction after temporary removal of their tracheostomy cannula. VNEP is an effective, non-invasive, treatment in infants with CHS if initiated before tracheostomy. It may improve the children's quality of life during the daytime. If upper airway obstruction is a problem in the first year of life, it may be combined with nasal mask CPAP.